EMPIRICAL ANALYSES ON THE “UNDERWRITING CYCLE”: AN EVALUATION - Venezian, Emilio (Assurances, 2002)
A number of papers on the underwriting cycle have appeared in the literature in the last 15 years. Despite the reviewing process many of these papers have potentially serious problems. Subsequent writers have cited the earlier work uncritically and sometimes perpetuated the errors in their own work. This article points out four problem areas and discusses some of the effects. One potentially far-reaching problem has been the neglect of taxation issues in the financial models used to motivate analysis. If the financial models are incomplete by ignoring taxes then the premium to surplus ratio becomes an omitted variable and adding such variables related to it in empirical analyses could lead to spurious regression due to the misspecification. Other problems include the use of dangerous statistical methods without proper safeguards, the use of data that are inappropriate for the intended application.